Exploring the challenges in classroom assessment: A mixed-method study of secondary schools in Pakistan - Syed Kamran Ali Shah; Muqaddas Butt; Ayesha Saleem; Muhammad Usman Rafique (Institute of Advanced Engineering and Science, 2023)
In the process of classroom assessment, data is collected regarding the skills, understanding and knowledge of students. It has very important role in enhancing academic achievement of students. Present study was designed at exploring the challenges of classroom assessment. The sample of study contained a sample of 360 participants and a concurrent mixed-method design was deployed to conduct the research. Data collection was carried out using researchers’ self-developed questionnaire. The collected data was analyzed using statistical software of SPSS version 24.0 for descriptive and inferential stats. For collection and analyses of qualitative data, classroom observation and semi-structured interviews were also conducted. The study explored those major challenges included lack of interest of both, the parents and the students; insufficient guidance on the assessment by school administration; and less or no provision of professional training in assessment to the teachers. It was recommended that the school administration should take appropriate steps for the involvement of all stakeholders. Extensive professional training should be provided to all the teachers on regular basis by the concerned departments.